TINJAUAN MAINAN LOKAL MENGGUNAKAN KECENEDERUNGAN BASIC NEEDS DESIGN, SOCIAL NEEDS DESIGN DAN LOCAL WISDOM DESIGN - Hady Soedarwanto (Narada : Jurnal Desain dan Seni, 2019)
The toy product industry is currently stretching and becoming one of the major companies in the world. Those industries are still monopolized by developed countries. Developing countries such as Indonesia have the opportunity to participate in the competition of the toy product industry. The way to deal with the problem is by developing existing potential by utilizing existing local wisdom. Through research on local toys, it is expected to be an opportunity for the possibility of that competition. By using three phenomena in design is expected to open many changes for many new possibilities in the toy industry. The design phenomena are the basic needs tendency (Vitruvius Theory), social needs tendencies (Sir Henry Wotton's theory) and local wisdom tendencies (Viktor Papanek, Schulz and Y.B.Mangunwijaya's Theory). The theory is used to extract the values of basic needs, social needs and local wisdom that is typical of the toy in order to get the variables of the design requirements to be used in the development of scientific design, especially toy product design. The results of this study get about how the design fulfills its basic needs, fulfills its social needs and raises the value of its local wisdom.